The Impact of Tablet Use on the Academic Performance of Students in the Faculty of Applied Sciences and Technology - Nursyaza Nabihah Binti Abd Malek,; Dr. Norhaidah Binti Mohd Asrah, (Enhanced Knowledge in Sciences and Technology, 2024)
Ministry of Education has launched a program called PerantiSiswa Keluarga Malaysia to provide tablets for students from B40 families for pursuing higher learning. Thus, this research aims to determine the relationship between tablet usage and demographic characteristics among Faculty of Applied Science and Technology (FAST) students by using the Chi-square test, study relationship between tablet usage with students’ academic performance by using the cross tabulation and Cramer’s V analysis, and identify the factors influence students on using tablet for learning by using factor and path analysis. A survey of 218 respondents revealed that tablet usage has correlation with gender, programme, household income group, and PerantiSiswa recipients. Furthermore, the finding shows that the cumulative gred point average (CGPA) has the strongest relationship with tablet use for study, fully attention in class has strongest relationship with time spent on tablet, and time management has has strongest relationship with tablet application. Six factors influencing tablet use in education were identified among 25 variables which are the academic performance, motivation, enjoyment, social support, educational utility, and communication. The connection between these six factors are analyzed by using the path analysis and the result confirmed that all factors had impact on motivation and enjoyment of using tablet. In conclusion, tablets have potential to change the way teaching and learning in education, but how effective the impact can be seen on the student’s academic performance. In future studies, it should consider all faculties in UTHM and investigate the impact of PerantiSiswa on learning outcomes through their test scores and critical thinking abilities.